MADURA LANGUAGE VARIATIONS IN CHILDREN AND ADULTS IN MANDURO VILLAGE SEEN FROM PHONOLOGICAL CHANGE AND ITS RELATIONSHIP WITH LANGUAGE CHANGE AND ETHNIC IDENTITY - Setiawati, Ety; Widodo, Wahyu; Warsiman, Warsiman; Sukmawan, Sony; Ardhian, Dany (International Journal of Humanity Studies (IJHS), 2019)
Manduro Village has a similar name to Madura Island. The similarity of the name positively correlates with the likeness of language and local culture. They call themselves Oreng Manduro 'Madurese'. The language used by residents is the Madurese Language (after this referred to as ML). This study aims to look at variations of language from the social perspective, in the form of age and ethnic main variables. Of the two variables, changes in MLÂ  spoken by adults with what children say and how social contact affects these changes are also examined. This research is descriptive-qualitative research with the leading theory of socio-dialectology. The research data was taken from the informants selected by purposive sampling using the Swadesh list. Data retrieval technique is by recording and note-taking. The results show that ML that is spoken by adults and children has a difference. Differences are seen in phonological terms so that they appear to cause the differences and changes in both. From the total data found, phoneme changes significantly occur in phonemes / É› / to phonemes / á´ /. Phonemes / É› / are phonemes spoken by ML speakers of adult age, while phonemes / á´ / are phonemes spoken by children in the same lexicons.DOI:Â 10.24071/ijhs.2019.020206